Systematically visualizing ChatGPT used in higher education: Publication trend, disciplinary domains, research themes, adoption and acceptance - Ma, Ting (Computers and education. Artificial intelligence, 2025)
Since it was released in November 2022, ChatGPT has been exerting revolutionary influence on the realm of higher education. In order to obtain a comprehensive understanding of the research landscape, we conduct a systematic literature review on the studies of ChatGPT used in higher education. Both quantitative and qualitative methods were adopted to bibliometrically examine the included literature selected from Web of Science and Scopus through the PRISMA protocol. Tools of VOSviewer and CitNetExplorer were employed to visualize the citation information. Our findings showed that the recent two years witnessed an ever-growing popularity of this research theme. Citation information analysis reveals the most influential authors, countries, sources, organizations and four focused topics. The disciplinary distribution of related research indicates a wide range of categories. More importantly, ChatGPT was found to be versatile in assisting teachers, students and researchers with a variety of tasks, and the factors influencing the acceptance of this technology among college students could be investigated through models like TAM, UTAUT and their extensions. We suggest future studies to focus on the ways to address the limitations and ethical issues of ChatGPT through AI literacy cultivation and joint efforts of all stakeholders. •Upward publication trend shows growing popularity of ChatGPT in higher education.•ChatGPT's capabilities excel in lower-level thinking but fall short in high-level skills.•ChatGPT enhances higher education as a assistant in teaching, learning and research.•Extended frameworks predict ChatGPT's adoption by considering various determinants.